(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Monitoring, recording and evaluating the work of students is an integral part of the organization of educational practice. As a result of the final report of the internship, it is advisable to draw conclusions about the theoretical and practical readiness of students for educational work at school, to assess the quality of work on the organization of internships by higher education and school staff, to identify measures for further improvement. In assessing the work of students, first of all, it is necessary to take into account the level of theoretical and practical preparation of the future teacher for independent pedagogical activity.